The identification of a cis-acting element involved in cyclic 3‘,5‘-adenosine monophosphate regulation of bovine vasopressin gene expression - Pardy, K; Adan, R.A.; Carter, D.A.; Seah, V; Burbach, J.P.; Murphy, D (The Journal of biological chemistry, 1992)
Cyclic adenosine 3‘,5‘-monophosphate (cAMP) has been implicated as an intracellular messenger mediating osmotic regulation of expression of the gene encoding the neuropeptide vasopressin (VP) in the hypothalamus. We have used a heterologous transient transfection system to demonstrate that cAMP regulates the bovine VP gene promoter following transfection into CV1 cells. Mutational analysis identified a bovine VP cAMP-responsive element (BVP-CRE) 120-112 base-pairs upstream of the start of transcription. DNase I footprint analysis using nuclear protein extract from CV1 cells showed protection at the site of the BVP-CRE. Protection of the BVP-CRE was also observed using purified AP1 protein, while there was a weak interaction with the BVP-CRE using purified rat CREB protein. Nuclear proteins purified from the rat supraoptic nucleus bind to the BVP-CRE. As transgenic mouse studies have shown that the bovine VP gene is subject to appropriate physiological regulation in the mouse hypothalamus (Ang, H. L., Funkhouser, J., Carter, D. A., Ho, M. Y., and Murphy, D. (1991) Soc. Neurosci. Abstr. 513, 12), these data indicate a role for the BVP-CRE element in mediating VP gene expression in vivo. These data demonstrate that cAMP regulates bovine VP gene expression in vitro via a cis-acting element within the VP promoter, and this activation may be mediated by members of the AP1/ATF/CREB family of transcription factors.